The effect of foreign labour involvement on the Malaysian construction project performance / Florina Salleh - Florina , Salleh (2013)
Supply of a local construction labour has been all along a shortage in construction industry due to their lack of interest to work as a construction labourer. The main reason could be due to the 3D’s perceptions, ie. dirty, dangerous and difficult. At the same time developers and main contractors prefer to award their sub-contract directly to the foreign labour rather than to the small scale sub-contractor as cost for direct award is cheaper and therefore definitely increasing their profit margin. This research is to systematically identify the important factors that need to be considered in selecting foreign labour, their allocation into different trades and to discuss how is the foreign workers characteristics that's includes compliance to government guidelines, type of expertise, level of expertise and origin correlated with project performance. Hence, one hundred (100) set of questionnaire survey was distributed in Klang Valley to explore the foreign labour involvement in every trades of construction activities. In addition to this questionnaire survey, a selected 10 industrial experts were interviewed to validate data that had been collected. Data was analysed using average index method, frequency analysis, descriptive analysis and bi-variate spearman rank correlation analysis by Statistical Package for Social Science (SPSS) software. From the findings, it shows that more involvement of foreign labour had been identified for architectural and structural works. Most of the foreign labours are from Indonesia. The distribution of foreign labour was effected by the compliance of government guidelines, type of expertise, level of expertise and origin. Result from the survey data analysis is that the origin and level of expertise of foreign labour from Indonesia do have a significant correlations with project performance in terms of work completed on time, good workmanship and less defects. Foreign labour from China have significant correlations with project performance in terms of good workmanship. Other origin doesn’t have any significant correlations. Type of expertise of foreign labour have a significant correlations with project performance in terms of good workmanship and less defects but not correlated with work completed on time and budget. Existing approach implemented by the Government is having significant correlations with project performance.